Destination branding and visitor loyalty: The case of agrotourism - Evangelos Christou; Chryssoula Chatzigeorgiou; Ioanna Simeli (TOURMAN 2018 Conference Proceedings, Rhodes, Greece, 25-28 October 2018, 2018)
It has been established that strong destination brands are important in the agrotourism industry. Agrotourism brands provide the link between visitors and the agrotourism firms and destination, and tourists may or may not develop a degree of loyalty to relevant brands. The present study suggests that confidence in an agrotourism brand has high influence in development of brand loyalty. Based on hypotheses developed, confidence in an agrotourism brand is influenced by brand characteristics, agrotourism company characteristics and visitor characteristics. The present survey took place in Greece and examined the attitudes of visitors in agrotourism firms at the island of Lesvos. Survey results demonstrate that agrotourism firm brand characteristics appear more important in their impact on a visitor's confidence in a brand. It was also established that confidence in a brand is positively influencing loyalty. Recommendations are developed for agrotourism marketers in relation to building and maintaining visitor confidence in a brand.
Keywords: L83; Z31; Z33; 330; agrotourism; brand confidence; destination branding; brand loyalty